The Cambridge introduction to William Faulkner - Towner, Theresa M (Cambridge University, 2013)
This introductory book provides students and readers of Faulkner with a clear overview of the life and work of one of America's most prolific writers of fiction. His nineteen novels, including The Sound and the Fury, As I Lay Dying, Go Down, Moses, and Absalom, Absalom!, are discussed in detail, as are his major short stories and nonfiction. Focused on the works themselves, but also providing useful information about their critical reception, this Introduction is an accessible guide to Faulkner's challenging and complex oeuvre.